Analysis of The Supreme Court's Decision in Case No. 916/PDT.P/2022/PN.SBY in Granting The Application for Registration of Interfaith Marriages in The Perspective of Marriage Law No. 1 of 1974 - Nugroho Putra Liyanto; M. Junaidi (Proceeding International Conference Restructuring and Transforming Law, 2023)
Indonesia is a country with multi-religious citizens. The large variety of religions and beliefs held by Indonesians makes it possible for them to have heterosexual marriages. Marriage regulations in Indonesia are stated in Law No. 1 1974 concerning marriage. How the place of marriage between different religions in the law is still a matter of debate. There is an article that says that about marriage between different religions. The decision of the Supreme Court of the Republic of Indonesia regarding accepting the request for freedom from marriages of different religions. The Surabaya District Court is the entry point for the legal legitimacy of marriages of different religions in Indonesia. The purpose of this article is to review and analyze the Supreme Court's decision in issuing a request for registration of marriages between different religions at the Surabaya District Court, and examine the legal position of marriages between different religions in Law Number 1 of 1974 concerning Marriage and the Compilation of Islamic Law. Studying it is a normative study using legal methods in Indonesia. Based on the analysis of legal hardware, it is found that marriages of different religions according to Indonesian marriage law are prohibited and declared invalid.